Proteína C reactiva y enfermedad arterial coronaria. C reactive protein and coronary artery disease. - Flor de la C. Heres Álvarez; Amalia Peix González; Roger Ravelo Dopico; Omar González Greck (ECIMED, 2011)
Taking into account the crucial roll of the inflammatory process in the formation, progressionand development of atherotrombosis, many inflammatory markers have been studied to improvethe coronary risk stratification in primary and secondary prevention. C reactive protein,determined by a highly sensitive method, has been one of the most thoroughly evaluated.Its utility as a strong predictor of cardiovascular events in healthy people, or as apredictor of recurrence in patients with stable coronary artery disease or acute coronary syndromeshas been demonstrated. The aim of this paper is to revise the biological characteristicsas well as the methods to determine the C reactive protein, and its relation with the cardiovascularrisk factors and coronary artery disease.